URGENSI PENDIDIKAN KEWIRAUSAHAAN DI PERGURUAN TINGGI - Taqiyudin Subky (STAI Sufyan Tsauri Majenang, 2020)
This article is simply discussing about the need of entrepeneurship education in higher education institution. The main characteristics of an entrepreneur were described as confidence, task and result oriented, risk seeker, leadership, originality and future oriented. By knowing these characteristics, we can derive the role of a higher education institution in entrepreneurship development. The integration of the competency based education and the entrepreneurship concept should be the new paradigm in higher education institution toward the globalization era.